Measuring wellbeing and sustainable HRM in Mexico - Rubio Leal, Yanira Lizeth; Madero Gómez, Sergio Manuel (Universidad Autónoma de Nuevo León, 2022)
The purpose of this paper is to elaborate an empirically based comprehensive scale for measuring sustainable HRM and wellbeing, how it’s perceived by 120 employees in the northern of Mexico?. The research gathers information on well-being and Sustainable HRM, and attend to drive theory, yielding sustainable needs focus on the economic, environment and social categories. The research further predicts that greater wellbeing programs increase sustainable HRM programs in enterprises. A Varimax factor analysis is presented to determine which latent variables can be present to assess the validity of four dimensions comprising the construct of perceived sustainable HRM and Wellbeing in an exploratory analysis and confirmatory factorial model. The scales are composed by a questionnaire of 30 items. Finally, the research provides evidence through a SEM test that High Sustainability companies significantly has greater well-being programs that could lead future research..